A study of phase-steepened Alfvén waves in a high-speed stream at 0.29 AU - P. Alexander; P. Alexander (Annales Geophysicae, 2000)
This work performs a search of phase-steepened Alfvén waves under a priori ideal conditions: a high-speed solar wind stream observed in one of the closest approaches to the Sun by any spacecraft (Helios 2). Five potential candidates were initially found following procedures established in earlier work. The observed cases exhibited arc-like or elliptical polarizations, and the rotational discontinuities that formed the abrupt wave edges were found at either the leading or the trailing part. The consideration of some additional specific parameters (mainly related to the relative orientation between mean magnetic field, wave and discontinuity) has been suggested here for an ultimate and proper identification of this kind of phenomenon. After the inclusion of these calculations in our analysis, even fewer cases than the five originals remain. It is suggested that optimum conditions for the detection rather than just for the existence of these events have to be reconsidered. Key words: Interplanetary physics (discontinuities; MHD waves and turbulence; solar wind plasma)